Kemagnetan: konsep, sifat, dan penerapannya dalam kehidupan - Zunnur, Haafidzah Ghaniy Zayn (Maliki Interdisciplinary Journal, 2026)
The concept of magnetism is an important part of physics that discusses how an object can attract or repel other objects that have magnetic properties. This phenomenon is related to the existence of a magnetic field that arises due to the movement of electrons in certain materials. Magnets come in various forms, such as bars, horseshoes, rings, and compass needles, each of which is used according to its function and purpose. Based on their source, magnets are classified into natural and artificial magnets, with artificial magnets being more widely used because their strength and stability can be controlled. Magnets have distinctive properties, such as always having two poles, namely a negative south pole and a positive north pole, only attracting certain ferromagnetic materials, and being able to indicate the direction of the Earth. In addition, magnetic properties can be obtained through direct rubbing, induction, or the use of electric current, and their magnetic properties can be lost due to heating or impact. The application of magnets is very broad, ranging from simple tools such as compasses and refrigerator covers to complex technologies such as electric motors, generators, audio devices, and industrial systems. Understanding magnetism allows students to not only learn basic physics concepts, but also understand how these scientific principles play a role in the technology they use every day.